DIGITALPRENEUR POTENTIAL ANALYSIS OF EDUCATIONAL STUDENTS - Perwita, Dyah; Widuri, Retno; Afif, Nur Choirul; Thoha, Didik Ahmad (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
Indonesia is currently in the creative and digital economy stage in the developmentof the industrial economy. Reflecting on information and communicationtechnology in the era of the industrial revolution 4.0 which is developing veryrapidly, the opportunity to create digital enterpreneurs is quite large. Highereducation is one of the institutions tasked with creating a superior generation thatis able to contribute its thoughts to the progres of the Indonesian nation. This studyaims to determine the potential of digital enterpreneurs (digipreneurs) in educationstudents at Jenderal Soedirman University, and develop the Indonesian economythrough digitalization of education. This study used a qualitative approach whichwas carried out through several stages, namely: data presentation, data processing,research findings, and discussion of research findings. Data collection techniquesusing interviews, observation, questionnaires, and documentation. The results ofthe study illustrate that education students have the potential to becomedigitalpreneurs in the field of education with a variety of bussiness ideas, such asonline tutoring, content creators through the Youtube platform, digital schoolequipment bussinesses,building start-up companies in the field of education andcounseling, building platforms mentoring students, establishing an EspostAcademy, becoming a writer or editor of a blog site or website regarding education,and building an educational start-up company.Keywords: Digital Enterpreneur; Digipreneur; Digitalpreneur; EducationalStudent; Enterpreneur